Analisis Pengelolaan Pajak Daerah di Kabupaten Barru - Nurul Hilal Bahnar; Andi Gau Kadir (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2018)
This study aims to describe and analyze how the performance of the Regional Income Agency in the management of local taxes in Barru regency and to analyze what factors affect the management of local taxes that do not reach the target and that exceed the target in Barru regency. The results show that the management of Local Taxes in Barru District has not been effective. It is shown that the target and realization of local tax revenues have not reached the target and some even exceed the target. The factors that cause it are: 1) Planning done by the Regional Revenue Board is less than maximum because so many other activities undertaken by the Regional Revenue Board. 2) Organizing undertaken by the Regional Revenue Board is not maximal because the number of personnel or tax officers owned is very limited. 3) In the stage of mobilization or implementation in tax management is also less than the maximum because some of the taxpayers do not want to pay taxes in accordance with the imposition of a predetermined tax. 4) Supervision conducted by the Regional Revenue Agency is not maximal due to the large number of taxpayers who must be supervised or controlled.